FAKTOR YANG BERHUBUNGAN DENGAN KELELAHAN KERJA PADA PERAWAT - Kadir, Abd; Ilyas, Muhammad; Putra, Ryryn Suryaman Prana; Saputri, Agnes Ratna (Ensiklopedia of Journal, 2025)
Abstract: Work fatigue experienced by nurses is one of the significant factors that can reduce the quality of health services and increase the risk of errors in medical actions. Nurses who experience fatigue tend to show a significant decrease in performance, both in terms of the effectiveness of nursing actions and productivity in providing health services. The purpose of the study was to determine the factors associated with job fatigue in nurses. The research design used in this study was cross sectional. The research was conducted at RSU Haji Medan in July 2024. The study population was all inpatient nurses at RSU Haji Medan which amounted to 227 people. The sample amounted to 119 respondents. The sampling technique used Simple Random Sampling. The research instrument used a research questionnaire. Data analysis was performed univariate and bivariate. The results showed a relationship between age (p value: 0.032) and workload (p value: 0.01) to job fatigue in nurses. It is recommended that hospital management organize work recreation activities or rotate nurses who are old and less productive with nurses who are young and still productive.Keywords: Occupational Fatigue, Age, Nurses.Azizah, N., Millah, I., Kusumaningtiar, D, A., Keumala, C, A. (2023). Faktor – Faktor Yang Berhubungan Dengan Kelelahan Kerja Pada Perawat Di Rumah Sakit Zainuttaqwa Kota Bekasi. Jurnal Multidisiplin Indonesia. Vol 2. No. 9. Gumelar, H., Kusmiran, E., Haryanto, M, S. (2021). Hubungan Beban Kerja Dengan Kelelahan Kerja Pada Perawat Pelaksana Di Instalasi Rawat Inap. JPPNI. Vol 6. No. 2. Handayani, P., Hotmaria, N. (2021). Hubungan Beban Kerja Dengan Kelelahan Kerja Pada Perawat. Indonesian Journal of Nursing Health Science. Vol 6. No. 1. Hidayat, L., Kadir, A, R., Diniati, R. (2023). Hubungan Usia, Jenis Kelamin Dan Status Pernikahan Terhadap Kelelahan Kerja Perawat Covid-19 Di Rsud Labuang Baji. Journal of Health, Education and Literacy. Vol 5. No. 2. Pakpahan, D, M., Suangga, F., Utami, R, S. (2024). Hubungan Karakteristik Perawat Dan Beban Kerja Dengan Kelelahan Kerja Perawat Di Ruang Rawat Inap RSUD Kota Tanjungpinang. Jurnal Rumpun Ilmu Kesehatan. Vol 4. No. 1 Rudyarti, E. (2020). Analisis Hubungan Stres Kerja, Umur, Masa Kerja Dan Iklim Kerja Dengan Perasaan Kelelahan Kerja Pada Perawat. Seminar Nasional Kesehatan Masyarakat.